Sulfide solid electrolyte, solid electrolyte composite, and solid-state battery
Patent Information
- Application Number
- JP2022153093
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-26
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2042-09-26
AI Technical Summary
【0007】 本開示によれば、優れたイオン伝導度と、低い硫化水素発生量とが両立した硫化物固体電解質、固体電解質複合体、及び固体電池が提供される。
Smart Images

Figure 0007652166000002 
Figure 0007652166000003 
Figure 0007652166000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sulfide solid electrolyte, a solid electrolyte composite, and a solid-state battery. [Background technology]
[0002] Conventionally, solid-state batteries have been known as lithium-ion secondary batteries with excellent safety. Patent Document 1 discloses a sulfide solid electrolyte used in solid-state batteries. The sulfide solid electrolyte disclosed in Patent Document 1 contains Li, P, S, and N elements, and has a composition represented by the following general formula: General formula: xLi2S-yP2S5-zLi3N (44≦x≦54, 30≦y≦32, 16≦z≦24, x+y+z=100) Patent Document 1: [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-67613 A Summary of the Invention [Problem to be solved by the invention]
[0004] A sulfide solid electrolyte may generate hydrogen sulfide when it comes into contact with water, and therefore a sulfide solid electrolyte that has both excellent ionic conductivity and a low amount of hydrogen sulfide generated is required.
[0005] The present disclosure has been made in consideration of the above circumstances. An object of one embodiment of the present disclosure is to provide a sulfide solid electrolyte, a solid electrolyte composite, and a solid-state battery that combine excellent ion conductivity with a low amount of hydrogen sulfide generation. [Means for solving the problem]
[0006] Means for solving the above problems include the following embodiments. <1> Contains Li, P, S, and A elements, PS4 3- Structure and AS2 2- The structure is It is a sulfide glass, The sulfide solid electrolyte, wherein the element A includes at least one of an element Ge, an element Sn, and an element Pb. <2> It has a composition represented by Li3PS4 and Li2AS2, The ratio of Li3PS4 to the total of Li3PS4 and Li2AS2 is 60 mol% to 80 mol%. <1> The sulfide solid electrolyte according to claim 1. <3> The A element includes a Ge element. <1> or <2> The sulfide solid electrolyte according to claim 1. <4> The above <1> ~ <3> A second sulfide solid electrolyte having a higher ionic conductivity than the first sulfide solid electrolyte, which is the sulfide solid electrolyte according to any one of the above items. The first sulfide solid electrolyte covering at least a portion of a surface of the second sulfide solid electrolyte; A solid electrolyte composite comprising: <5> a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; At least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer is <1> ~ <3> The sulfide solid electrolyte according to any one of the above items, <4> and the solid electrolyte composite according to claim 1. Effect of the Invention
[0007] According to the present disclosure, there are provided a sulfide solid electrolyte, a solid electrolyte composite, and a solid-state battery that combine excellent ion conductivity with a low amount of hydrogen sulfide generation. [Brief description of the drawings]
[0008] [Figure 1] An explanatory diagram for explaining the coordination relationship between Li3PS4 and Li2AS2 is shown. [Diagram 2]1 shows graphs of Raman spectroscopy spectra of the sulfide solid electrolytes of Example 4, Comparative Example 1, and Comparative Example 2. [Diagram 3] 1 shows graphs of spectra obtained by X-ray photoelectron spectroscopy (XPS method) of the sulfide solid electrolytes of Example 1, Example 4, and Comparative Example 2. [Figure 4] 1 shows graphs of spectra obtained by X-ray photoelectron spectroscopy (XPS method) of the sulfide solid electrolytes of Example 1, Example 4, and Comparative Example 2. [Diagram 5] 1 shows graphs of X-ray diffraction (XRD) spectra of the sulfide solid electrolytes of Examples 1 to 4. [Figure 6] 1 is a graph showing ion conductivity and amount of hydrogen sulfide generated versus composition of sulfide solid electrolytes of Examples 1 to 4, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified. In the present disclosure, the term "step" refers not only to an independent step, but also to a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.
[0010] (1) Sulfide solid electrolyte The sulfide solid electrolyte of the present disclosure contains Li, P, S, and A elements, and is PS43- Structure and AS2 2- The glass has a structure of sulfide glass, and the element A includes at least one of a Ge element, a Sn element, and a Pb element.
[0011] In the present disclosure, the term "sulfide glass" refers to a material synthesized by amorphizing raw materials, and refers not only to strict "glass" in which no crystalline periodicity is observed in X-ray diffraction measurements, etc., but also to all materials synthesized by amorphizing through mechanical milling, etc. Therefore, even if a peak derived from a raw material (such as Li2S) is observed in X-ray diffraction measurements, etc., the material is classified as sulfide glass as long as it is synthesized by amorphizing. "The sulfide solid electrolyte is sulfide glass" means that 95% by mass or more of the sulfides forming the solid electrolyte are sulfide glass, and the solid electrolyte contains almost no glass ceramics or ceramics. More preferably, the sulfide solid electrolyte contains 99% by mass or more of sulfide glass. In the present disclosure, the term "glass ceramics" refers to a material obtained by crystallizing sulfide glass. Whether or not a material is a glass ceramic can be confirmed by, for example, X-ray diffraction. A sulfide glass-based material having a crystallinity of 60% to 80% as measured by X-ray diffraction is considered to be a glass ceramic.
[0012] The sulfide solid electrolyte of the present disclosure has the above-mentioned configuration, and therefore achieves both excellent ion conductivity and a low amount of hydrogen sulfide generated. This effect is believed to be due to, but not limited to, the following reasons. Conventional sulfide solid electrolytes with high ionic conductivity contain PS4, which is easily reactive with water, in their structure. 3- When water is adsorbed onto the surface of a sulfide solid electrolyte, the OH - PS4 3- This causes nucleophilic attack on the PS structure. 4-x -O xIt is known that hydrogen sulfide is generated at the same time as the change to hydrogen sulfide. Furthermore, according to the HSAB (Hard and Soft Acid and Base) rule, it is thought that P, which is a hard acid, and O, which is a hard base, are prone to Coulomb interactions and can easily bond together. The sulfide solid electrolyte of the present disclosure is AS2 2- It has a structure. AS2 2- A in Structure 2+ , PS4 3- P of Structure 5+ Since it has a lower charge, a smaller atomic radius, and is more polarizable than O, it is a soft base. 2- It is difficult to bond with HO and has low reactivity with HO. On the other hand, PS4 3- The structure is highly reactive with H2O. However, AS2 2- As shown in Figure 1, by mixing with the structure, the PS bond, which is weak in water, is partially A 2+ As a result, PS4 3- The skeleton becomes less likely to react with H2O, improving water resistance. In addition, the ionic conductivity is ensured by Li3PS4, which has high ionic conductivity, and the Li2AS2 framework also has PS bonds in the A 2+ By coordinating with Li4AS4, a structure similar to Li4AS4 with high ionic conductivity is formed, and the overall ionic conductivity is 10 -4 Achieve mS / cm order. As a result, it is presumed that the sulfide solid electrolyte of the present disclosure has both excellent ionic conductivity and a low amount of hydrogen sulfide generated.
[0013] The sulfide solid electrolyte of the present disclosure may or may not contain elements other than the Li element, the P element, the S element, and the A element, as necessary.
[0014] The element A preferably contains a Ge element, and is preferably a Ge element, which allows the sulfide solid electrolyte to have both superior ion conductivity and a lower amount of hydrogen sulfide generated.
[0015] The sulfide solid electrolyte may have a composition represented by Li3PS4 and Li2AS2. Li2AS2 may be one type or two or more types depending on the type of element A. The ratio of Li3PS4 to the total of Li3PS4 and Li2AS2 (hereinafter, simply referred to as "the ratio of Li3PS4") is not particularly limited, and is preferably 20 mol% to 80 mol%, more preferably 40 mol% to 80 mol%, and further preferably 60 mol% to 80 mol%.
[0016] The sulfide solid electrolyte has a composition represented by Li3PS4 and Li2AS2, and the ratio of Li3PS4 is preferably 40 mol% to 80 mol%, which allows the sulfide solid electrolyte to further reduce the amount of hydrogen sulfide generated while maintaining excellent ion conductivity.
[0017] The shape of the sulfide solid electrolyte may be, for example, particulate. The particle size of the sulfide solid electrolyte is not particularly limited, but is preferably 0.05 μm to 3.0 μm. This can further reduce the battery resistance of the solid battery. The particle size of the sulfide solid electrolyte is measured by dispersing the object to be measured in a dispersion medium, measuring the volumetric particle size distribution using a particle size distribution measuring device, and determining the particle size at which the obtained volumetric cumulative particle size distribution value is 50%.
[0018] (2) Solid electrolyte complex The solid electrolyte composite of the present disclosure includes a second sulfide solid electrolyte (hereinafter also referred to as a "sulfide solid electrolyte (core)") having higher ionic conductivity than a first sulfide solid electrolyte, which is the sulfide solid electrolyte of the present disclosure, and the first sulfide solid electrolyte (hereinafter also referred to as a "sulfide solid electrolyte (shell)") covering at least a portion of a surface of the second sulfide solid electrolyte.
[0019] The solid electrolyte composite of the present disclosure has the above-mentioned configuration, and therefore achieves both excellent ion conductivity and a low amount of hydrogen sulfide generated. This effect is believed to be due to, but not limited to, the following reasons. The solid electrolyte composite has a sulfide solid electrolyte (core) that has a higher ionic conductivity than the sulfide solid electrolyte (shell). Therefore, the ionic conductivity of the solid electrolyte composite is excellent. Furthermore, the sulfide solid electrolyte (shell) covers at least a part of the surface of the sulfide solid electrolyte (core). Therefore, the sulfide solid electrolyte (core) is less likely to come into contact with water and is less likely to generate hydrogen sulfide. As a result, it is presumed that the solid electrolyte composite of the present disclosure has both excellent ionic conductivity and a low amount of hydrogen sulfide generated.
[0020] The shape of the sulfide solid electrolyte (core) may be, for example, particulate. The combined particle size of the sulfide solid electrolyte (core) and the sulfide solid electrolyte (shell) is preferably 0.1 μm to 50 μm, more preferably 0.1 μm to 3 μm. The thickness of the sulfide solid electrolyte (shell) is preferably 1 nm to 100 nm, more preferably 1 nm to 50 nm. The method for measuring the combined particle size of the sulfide solid electrolyte (core) and the sulfide solid electrolyte (shell) is similar to the method for measuring the particle size of the sulfide solid electrolyte.
[0021] The solid electrolyte composite may be a powder made of a plurality of solid electrolyte composite particles. One solid electrolyte composite particle may be made of one sulfide solid electrolyte (core) particle and a plurality of sulfide solid electrolyte (shell) particles covering at least a part of the sulfide solid electrolyte (core) particle, or may be made of one sulfide solid electrolyte (core) particle and a layer containing a plurality of sulfide solid electrolyte (shell) particles covering at least a part of the sulfide solid electrolyte (core) particle. From the viewpoint of further reducing the amount of hydrogen sulfide generated, it is preferable that the sulfide solid electrolyte (shell) covers the entire surface of the solid electrolyte.
[0022] The material of the sulfide solid electrolyte (core) is 1.0×10 -3 S / cm~1.0×10 -2 It is preferable that the electrolyte is a sulfide electrolyte having an ionic conductivity of 1000 S / cm, for example, an LGPS type (e.g., Li 10 GeP2S 12etc.), Argyrodite type (e.g., Thio-LISICON, etc.), glass ceramics (e.g., Li7P3S 11 etc.)
[0023] The method for producing the solid electrolyte composite is not particularly limited, and examples thereof include a method in which a slurry containing a sulfide solid electrolyte (shell) and a known solvent is impregnated, coated, sprayed, dropped, or the like onto a sulfide solid electrolyte (core) and then dried; a mechanochemical method, and the like.
[0024] (3) Solid state battery The solid-state battery of the present disclosure includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer includes at least one of the sulfide solid electrolyte of the present disclosure and the solid electrolyte composite of the present disclosure.
[0025] The solid-state battery of the present disclosure has the above-described configuration, and thus can achieve both excellent ion conductivity and a low amount of hydrogen sulfide generated. This effect is presumably due to the same reasons as those for the effect of the sulfide solid electrolyte of the present disclosure, but is not limited thereto.
[0026] When a set of a positive electrode layer, a solid electrolyte layer, and a negative electrode layer is defined as a power generation unit, the solid-state battery may have only one power generation unit or may have two or more power generation units. When the solid-state battery has two or more power generation units, the power generation units may be connected in series or in parallel.
[0027] (3.1) Solid electrolyte layer The solid-state battery includes a solid electrolyte layer. The solid electrolyte layer may or may not include at least one of the sulfide solid electrolyte of the present disclosure and the solid electrolyte composite of the present disclosure.
[0028] (3.1.1) Solid electrolyte The solid electrolyte layer may contain a solid electrolyte different from the sulfide solid electrolyte of the present disclosure and the solid electrolyte composite of the present disclosure (hereinafter, also referred to as "other solid electrolyte"). Examples of the other solid electrolyte include a sulfide solid electrolyte different from the sulfide solid electrolyte of the present disclosure (hereinafter, also referred to as "other sulfide solid electrolyte"), an oxide solid electrolyte, a hydride solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, and the like. The other solid electrolyte may be used alone or in combination of two or more. From the viewpoint of excellent chemical stability, the other sulfide solid electrolyte preferably has an anion structure of an ortho composition as a main component of the anion structure. Examples of the anion structure of the ortho composition include PS4 3- Structure: SiS4 4- Structure, GeS4 4- Structure: AlS3 3- Structure or BS3 3- The structure is as follows. The other sulfide solid electrolyte may be amorphous or crystalline. When the other sulfide solid electrolyte is crystalline, the other sulfide solid electrolyte has a crystalline phase. Examples of the crystalline phase include a Thio-LISICON type crystalline phase, a LGPS type crystalline phase, and an Argyrodite type crystalline phase. The shape of the other solid electrolyte may be, for example, particulate. The particle size of the other solid electrolyte is not particularly limited, and is preferably 0.05 μm to 3.0 μm. The method for measuring the particle size of the other solid electrolyte is the same as that for the sulfide solid electrolyte.
[0029] (3.1.2) Binder The solid electrolyte layer may or may not include a binder. Examples of the binder include rubber-based binders such as styrene butadiene rubber, and fluoride-based binders such as polyvinylidene fluoride (PVDF).
[0030] (3.2) Positive electrode layer The solid-state battery includes a positive electrode layer. The positive electrode layer includes a positive electrode active material. The positive electrode layer may further include at least one of the sulfide solid electrolyte of the present disclosure, the solid electrolyte composite of the present disclosure, a positive electrode solid electrolyte, a conductive material, and a binder, as necessary. Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include rock salt layered active materials such as LiCoO2, spinel active materials such as LiMn2O4, and olivine active materials such as LiFePO4. Examples of the conductive material include carbon materials such as acetylene black, metal particles, conductive polymers, etc. Examples of the solid electrolyte and binder for the positive electrode layer include the same as those exemplified as other solid electrolytes and binders that can be included in the solid electrolyte layer.
[0031] [3.3] Positive electrode current collector The solid-state battery may further include a positive electrode current collector that collects current from the positive electrode layer and is disposed on the opposite side of the positive electrode layer from the solid electrolyte layer.
[0032] [3.4] Negative electrode layer The solid-state battery includes a negative electrode layer. The negative electrode layer contains a negative electrode active material. The negative electrode layer may contain at least one of the sulfide solid electrolyte of the present disclosure, the solid electrolyte composite of the present disclosure, a negative electrode solid electrolyte, a conductive material, and a binder, as necessary. Examples of the negative electrode active material include Li-based active materials such as metallic lithium, carbon-based active materials such as graphite, oxide-based active materials such as lithium titanate, and Si-based active materials such as simple Si. Examples of the conductive material, negative electrode solid electrolyte, and binder used in the negative electrode layer include the same conductive material, negative electrode solid electrolyte, and binder as those exemplified as the conductive material, positive electrode solid electrolyte, and binder that may be included in the positive electrode layer.
[0033] [3.5] Negative electrode current collector The solid-state battery may further include a negative electrode current collector that collects current from the negative electrode layer and is disposed on the opposite side of the negative electrode layer from the solid electrolyte layer. EXAMPLES
[0034] The present disclosure will be described in more detail below with reference to examples, but the invention of the present disclosure is not limited to these examples.
[0035] [1] Sulfide solid electrolyte [1.1] Example 1 As starting materials, lithium sulfide (Li2S), diphosphorus pentasulfide (P2S5), and germanium sulfide (GeS) were prepared. 3.072 parts by mass of Li2S, 4.247 parts by mass of P2S5, 1.000 parts by mass of GeS, and 33.28 parts by mass of dehydrated heptane were placed in a grinding vessel (volume: 45 mL). ZrO2 balls (diameter: 5 mm) were used as a planetary ball mill. 375 parts by mass of ZrO2 balls were placed in the grinding vessel and reacted at 500 rpm for 20 hours. After that, the mixture was dried at 100 ° C to obtain a sulfide solid electrolyte.
[0036] [1.2] Examples 2 to 4, Comparative Examples 1 and 2 A sulfide solid electrolyte was obtained in the same manner as in Example 1, except that the raw materials were mixed so that the molar ratio of Li3PS4 and Li2GeS2 was the ratio shown in Table 1.
[0037] [2] Analysis [2.1] Raman measurements Raman measurements were carried out on the sulfide solid electrolytes of Example 4, Comparative Example 1, and Comparative Example 2. The Raman measurements were carried out using "LabRAM HR" manufactured by Horiba, Ltd., with a laser wavelength of 532 nm. The measurement results are shown in FIG.
[0038] As shown in FIG. 2, in Comparative Example 1, -1 A peak appeared around the PS4 3- This is a vibration peak due to the structure. In Comparative Example 2, 370 cm -1 A peak appeared around 360 cm for GeS. -1 From the comparison with the vibration peak of GeS 2- This is a vibration peak due to In Example 4, PS43- 420cm due to the structure -1 Vibration peaks near 2- 370cm comes from -1 This is because the sulfide solid electrolyte of Example 4 is PS4 3- Structure and GeS2 2- The same is true for the sulfide solid electrolytes of Examples 1 to 3.
[0039] [2.2] XPS measurement XPS measurements were performed on the sulfide solid electrolytes of Example 1, Example 4, Comparative Example 1, and Comparative Example 2. The XPS measurements were performed using a "PHI 5000 VersaProbe II" manufactured by ULVAC Sales, Inc. The measurement results are shown in Figs. 3 and 4.
[0040] As shown in FIG. 3, in Examples 1 and 4, the same Ge as in Comparative Example 2 was used. 2+ In Examples 1 and 4, the peak due to Ge appeared at 30 eV to 31 eV. 4+ The peak due to this did not appear at 32 eV to 33 eV. 4, a peak also appeared at 160 eV to 162 eV in Examples 1 and 3. This peak had almost the same binding energy as the peak that appeared in Comparative Examples 1 and 2. From these results, the sulfide solid electrolytes of Examples 1 and 4 were 3- Structure and GeS2 2- The sulfide solid electrolytes of Examples 2 and 3 were found to have both the above structure.
[0041] [2.3]XRD measurement XRD measurements were carried out on the sulfide solid electrolytes of Examples 1 to 4. For the XRD measurements, Rigaku Corporation's "RINT-2000" was used, and the X-ray source was CuKα radiation. The measurement results are shown in FIG.
[0042] As shown in Fig. 5, in all of the XRD spectra of Examples 1 to 4, there were no diffraction peaks other than a small peak derived from the raw material Li2S. As a result, it was found that the main component of the sulfide solid electrolytes of Examples 1 to 4 was amorphous glass. From the results of the Raman measurement, XPS measurement, and XRD measurement, it was found that most of the starting materials were Li3PS4 and Li2GeS2.
[0043] [3] Evaluation [3.1] Measurement of ionic conductivity Approximately 100 mg of sulfide solid electrolyte is used at 6 tonnes / cm 2 The pellets were pressed at a pressure of 11.28 μm to obtain pellets having a thickness of about 500 μm. The thickness was measured using a micrometer.
[0044] The pellets were used to measure ionic conductivity. The ionic conductivity was calculated from the results of measuring AC impedance. The measurements were performed using a Solartron 1260 at a frequency range of 10 MHz to 1 kHz, an applied voltage of ±10 mV, and a temperature of 25°C. The measurement results are shown in Table 1 and Figure 6. In Figure 6, "x" indicates the proportion (mol%) of Li3PS4. The allowable range of ionic conductivity is 1.0 x 10 -4 S / cm or more.
[0045] [3.2] Measurement of hydrogen sulfide generation rate 5 mg of sulfide solid electrolyte was placed in a desiccator (volume: 1.5 L) kept in an environment with a temperature of 25°C and a dew point of -30°C and left to stand. The amount of hydrogen sulfide in the desiccator was measured using a hydrogen sulfide sensor (ToxiRAE Pro). The amount of hydrogen sulfide 30 minutes after the sulfide solid electrolyte was placed in the desiccator was recorded as the amount of hydrogen sulfide generated. The measurement results are shown in Table 1 and Figure 6. The acceptable range for the amount of hydrogen sulfide generated is 0.5 cc / g or less.
[0046] [Table 1]
[0047] In Table 1, "-" in the type column indicates that it has not been confirmed whether the glass is a sulfide glass or not.
[0048] The sulfide solid electrolyte of Comparative Example 1 was PS4 3- It has an AS2 structure. 2- Therefore, the amount of hydrogen sulfide generated in Comparative Example 1 was not within the allowable range. The sulfide solid electrolyte of Comparative Example 2 was AS2 2- Structure: PS4 3- Therefore, the ionic conductivity of Comparative Example 2 was not within the allowable range. From these results, it was found that the sulfide solid electrolytes of Comparative Examples 1 and 2 did not achieve both excellent ion conductivity and a low amount of hydrogen sulfide generated.
[0049] The sulfide solid electrolytes of Examples 1 to 4 contain Li, P, S, and Ge elements, and are PS4 3- Structure and GeS2 2- The glass has the structure of sulfide, and is a sulfide glass. Therefore, the ionic conductivity and the amount of hydrogen sulfide generated in Examples 1 to 4 were within the allowable range. From these results, it was found that the sulfide solid electrolytes of Examples 1 to 4 had both excellent ion conductivity and a low amount of hydrogen sulfide generated.
Claims
1. Contains Li, P, S, and A elements; P.S. 4 3- Structure and AS 2 2- The structure is It is a sulfide glass, The sulfide solid electrolyte, wherein the A element includes a Ge element.
2. Li 3 P.S. 4 and Li 2 A.S. 2 The composition is represented by Li 3 P.S. 4 and Li 2 A.S. 2 Li for the sum of 3 P.S. 4 The sulfide solid electrolyte according to claim 1, wherein the ratio of is 40 mol% to 80 mol%.
3. A second sulfide solid electrolyte having a higher ionic conductivity than the first sulfide solid electrolyte, which is the sulfide solid electrolyte according to claim 1; The first sulfide solid electrolyte covering at least a portion of a surface of the second sulfide solid electrolyte; A solid electrolyte composite comprising:
4. a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; 4. A solid-state battery, wherein at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer comprises at least one of the sulfide solid electrolyte according to claim 1 or 2 and the solid electrolyte composite according to claim 3.
Citation Information
Patent Citations
Sulfide solid electrolyte, lithium cell, and method for manufacturing the sulfide solid electrolyte
JP2011129407A
Sulfide-based solid electrolyte, manufacturing method of the same, and lithium-ion battery
JP2012043646A
Sulfide solid electrolyte
JP2019067613A
Tin-containing lithium phosphorus sulfide and method for producing the same
JP2022139139A
Preparing method for solid electrolyte, solid electrolyte made by the same, and all solid state battery including the same
KR1020170025617A